Glucomannan sponges: Effect of different amount of SLS and Sodium Hydroxide. - Fadilah Fadilah; Shidiq Trianto; Tri Nova Prakoso (Equilibrium Journal of Chemical Engineering, 2019)
Abstract.  An attempt to increase the economic value of porang flour was made by utilizing it for making of sponge. The sponge was made by direct foaming of glucomannan solution with the addition of SLS and NaOH. Dried sponge were obtained through freezing-thawing process followed by drying. The effect of amount of SLS and NaOH were investigated. It was found that increasing amount of SLS and NaOH made the cell size of the sponge smaller. While there was no tendency for swelling degree accordance to the various amount of SLS, the increasing amount of NaOH caused in increasing the swelling degree. Keywords: sponge, glucomannan, sodium laureth sulphate (SLS), sponge cell size, swelling degree.